2009
DOI: 10.1211/jpp.61.12.0005
|View full text |Cite
|
Sign up to set email alerts
|

Collagen-based wound dressing for doxycycline delivery: in-vivo evaluation in an infected excisional wound model in rats

Abstract: The study indicates that the developed dressing attenuated both infection and metalloprotease levels, and may therefore have potential application in wound healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Recent studies have shown the feasibility and more importantly the benefits of implants delivering antibiotics [208,209,210,211]. The delivery properties of collagen-based biomaterials also display great potential for ulcer treatment [197] and abdominal wall defect reconstruction [212,213,214].…”
Section: Recent Advances In Collagen-based Biomaterialsmentioning
confidence: 99%
“…Recent studies have shown the feasibility and more importantly the benefits of implants delivering antibiotics [208,209,210,211]. The delivery properties of collagen-based biomaterials also display great potential for ulcer treatment [197] and abdominal wall defect reconstruction [212,213,214].…”
Section: Recent Advances In Collagen-based Biomaterialsmentioning
confidence: 99%
“…In another approach, gelatin microspheres were conjugated to a catechol-type protease inhibitor, loaded with doxycycline, and incorporated into a collagen dressing [94]. Their ability to reduce MMP levels in the wound bed and prevent infection was evaluated in a bacteria-challenged excisional wound model in rats [95]. Finally, gelatin microparticles delivering FGF-2 were dispersed within a collagen sponge and enhanced angiogenesis and cell proliferation in a mouse model of pressure ulcers [96].…”
Section: Particlesmentioning
confidence: 99%
“…Then the cartilaginous tissue is replaced by bone tissue with the aid of the osteoblasts and the osteoclasts [45]. Thus, the early stages of skin wound healing are accompanied by accumulation of hexosamine [65] ( The progress of wound closure, collagen and hexozamine (as a marker for proteoglycans) contents were studied in the normal wounds comparing with the treated by gelatin microspheres with an antimicrobial agent. The characteristic property of the qualitative composition of glycosaminoglycans at the early stages of the embryogenesis of vertebral animals is the absence of keratan sulfate in all types of the cartilage models [57][58][59][60]; at this stage there is an increase in the content of chondroitin sulfates [60] and degree of glycosaminoglycan sulfation [61][62][63].…”
Section: Hyaluronan and Other Glucosaminoglycans In Cell Division MImentioning
confidence: 99%
“…The age-related qualitative and quantitative composition of glycosaminoglycans in different types of cartilage tissue has been quite well studied. The treatment accelerates the wound healing but does not change a dynamics of synthesis of proteoglycans and collagen [65]. As embryo development progresses, the content of keratan sulfate increases and the content of heparan sulfate decreases [60].…”
Section: Hyaluronan and Other Glucosaminoglycans In Cell Division MImentioning
confidence: 99%
See 1 more Smart Citation